EFFICIENCY OF ZAKAT MMANAGEMENT OORGANIZING (OPZ) IN INDONESIA - Aziz, Roikhan Mochamad (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2019)
National charity potential in Indonesia is very large, but not comparable to the fact that the number accumulation ZIS in Indonesia. Then, needs to be done to optimize the potential of zakat is one of them with efficiency. The purpose of this study was to determine the level of efficiency of Zakat Management Organization (OPZ). The sampling technique used in this research is purposive sampling by taking a sample of 2 organizations zakat is BAZNAS and PKPU. The data used in this research is secondary data obtained from financial statements published by BAZNAS and PKPU. Measurement of efficiency in this study using Data Envelopment Analysis (DEA).Input variables used in this study is the operational costs and personnel costs, while the output variable is the receipt and disbursement of zakat. Results from this study showed that only BAZNAS who always achieve efficiency levels of 100 percent during 2011-2013, while PKPU experiencing fluctuating conditions of efficiency. On average achievement BAZNAS efficiency from 2011 through 2013 is equal to 100 per cent, while the average achievement of efficiency PKPU fluctuated during the period 2011-2013 amounted to 52.13 percent.